The Struggle for Religious Ideologies in the Educational Institutions of Muhammadiyah and Nahdlatul Ulama: A Phenomenological Study in East Java - Mardiana, Dina; Umiarso, Umiarso; Thoifah, I’anatut (Universitas Islam Negeri (UIN) Fatmawati Sukarno Bengkulu, 2022)
This study focused on the phenomena or dynamics of the struggle for religious ideology that occur in the educational institutions (SMP/MTs and SMA/MA) of Muhammadiyah and Nahdlatul Ulama in East Java. Therefore, this study sought to see the internalization of the religious ideological values of Muhammadiyah and Nahdlatul Ulama in their education systems. Especially, when looking at clashes of religious thought that contain other ideologies (such as transnational (Salafi, Wahabi, and Shia), conservative/traditional, and reformist/modernist ideologies). This study used a qualitative approach and techniques for data collection used participatory observation, in-depth interviews, and documentation studies. The data analysis used the Miles, Huberman, and Saldana model consisting of four stages, namely, data collection, data condensation, data display, and conclusion. This study found that the educational institutions of Muhammadiyah and Nahdlatul Ulama have paradigmatic similarities, namely, ideology is positioned and functionalized as the motive and legitimacy of their educational actions and religious privileges. The expanding opportunities for dissemination and reproduction of other ideologies in their educational institutions are due to the very open nature of their religious understanding (Muhammadiyah has an understanding of Islamic Manhaji, and Nahdlatul Ulama has an understanding of Islamic mahzabi). Riset ini memfokuskan pada fenomena atau dinamika pergulatan ideologi keagamaan yang terjadi di kelembagaan pendidikan (SMP/MTs dan SMA/MA) Muhammadiyah dan Nahdlatul Ulama di propinsi Jawa Timur. Karenanya, riset ini berupaya melihat internalisasi nilai-nilai ideologis keagamaan Muhammadiyah dan Nahdlatul Ulama dalam sistem kependidikannya. Terutama ketika melihat benturan-benturan pemikiran keagamaan yang memuat ideologi lain (seperti ideologi transnasional (Salafi, Wahabi, dan Syi’ah), konservatif/tradisional, dan reformis/modernis). Riset ini menggunakan pendekatan kualitatif dengan teknik pengumpulan data memakai observasi partisipasi, wawancara mendalam; dan studi dokumentasi. Analisis datanya memakai model Miles, Huberman, dan Saldana yang terdiri dari empat tahap, yaitu: koleksi data, kondensasi data, display data, dan kesimpulan. Riset ini menemukan, kelembagaan pendidikan Muhammadiyah dan Nahdlatul Ulama memiliki persamaan paradigmatik, yaitu: ideologi diposisikan dan difungsionalisasikan sebagai motif serta legitimasi tindakan kependidikan dan privelege keberagamaan mereka. Pembentangan peluang diseminasi dan reproduksi ideologi lain di kelembagaan pendidikan mereka, disebabkan sifat pemahaman keagamaan mereka yang sangat terbuka (Muhammadiyah berpahaman Islam Manhaji, dan Nahdlatul Ulama memiliki pemahaman Islam mazhabi).